Mechanical and Topographical Characterization of Alginate Microcapsules - Virumbrales-Muñoz, María; Ochoa, Iñaki; Fernández, Luis (Jornada de Jóvenes Investigadores del I3A, 2023)
We used Atomic Force Microscopy (AFM) in order to characterize alginate microcapsules as for topography and stiffness. Thus, we intend to identify those which are theoretically most biocompatible by this technique, avoiding the need for animal testing.